The oxidation behaviour of mixed tungsten silicon sputtered coatings - Louro, C. (1999)
W-Si-N coatings were deposited by sputtering and their chemical composition, structure, thermal and oxidation behaviour were characterised. Si-containing films are essentially amorphous. W69Si31 film crystallises at 750 °C as [alpha]-W and W5Si3 phases whereas no significant structural transformations were observed for W24Si21N55 film up to 1000 °C, In both cases elemental diffusion (Si and N) for the substrate was detected after thermal annealing. These coatings present much better oxidation resistance than W and W45N55 coatings.